Can the Union of Prodrug Therapy and Nanomedicine Lead to Better Cancer Management?. Issue 1 (5th November 2021) - Muthiah, Giredhar; Jaiswal, Amit
Abstract : Prodrug‐mediated and nanomedicine‐mediated therapies stand at the forefront of cancer management today. However, a lot of recent research efforts have been focused on identifying novel strategies in treating tumor by combining the techniques and attributes of both prodrug‐mediated and nanomedicine‐mediated therapies into distinct prodrug‐based‐nanomedicine‐mediated (ProNaMed) therapies. Many of these amalgamated therapies exhibit augmented and sometimes synergistic antitumor effects which are engendered by the complementary and cooperative activities of the prodrugs and the nanostructures involved. Herein, the distinctive as well as overlapping features of prodrug‐mediated and nanomedicine‐mediated therapies with a few examples are expounded. Then, as some of the general trends observed in combined ProNaMed therapies are explored, the strategies used in such therapies along with some recent research examples and their respective therapeutic outcomes are discussed. Further, light is shed on the diverse manifestations of augmented antitumor effects and chemotherapeutic ameliorations which are noticeably materialized in many of the ProNaMed therapies. Fundamental insights are offered on why pursuing ProNaMed strategies may offer us better therapeutic solutions over isolated prodrug‐ or nanomedicine‐based strategies for tumor management. Abstract : Contemporary research trends are reviewed which focus on combining prodrugs and nanomedicine formulations (herein termed as ProNaMed therapies) for the management and treatment of cancers. The rationale behind such endeavors is discussed with multiple examples. This review also focuses on how ProNaMed therapies fare against conventional therapies.